234 Remote Surgical Teaching During COVID-19: Early Feedback from Students and Teachers. (4th May 2021) - Harris, H; Khera, G; Alanbuki, A r; Ray, K; Yusuf, W; Harvey, R
Abstract: Background: On the 23 rd March 2020 the government issued a nationwide lockdown in response to COVID-19. Using Microsoft Teams software, Brighton and Sussex Medical School transitioned to remote surgical teaching. We discuss the early feedback from students and tutors. Method: All students (N = 40) and tutors (N = 7) were invited to complete an online feedback survey. Results: Twenty students responded. Nine preferred remote teaching. The teaching was described as either good (10/20) or excellent (10/20). Small group teaching, lectures and student lead seminar sessions all received positive feedback. Students preferred sessions that were interactive. One hour was optimal (17/20). There was no consensus over class size. 15/20 (75%) would like remote teaching to continue after the pandemic. All tutors responded. There was a preference towards shorter sessions: 45 minutes (2/7) one hour (5/7). Tutors found virtual sessions less interactive (6/7). All tutors would like remote teaching to continue after the pandemic. Three suggested extending teaching to remote surgical ward rounds. Concern was raised by both students and tutors regarding the absence of practical skills. Conclusions: The value of remote teaching has been highlighted by COVID-19. Our feedback recommends a transition towards blended learning; using the convenience of remote teaching to help augment traditional medical school teaching.